Solvent solutions: comparing extraction methods for edible oils and proteins in a changing regulatory landscape. General introduction☆ - Carré Patrick; Berthold Sebastian; Piofczyk Thomas; Bothe Sarah; Hadjiali Sara (Oilseeds and fats, crops and lipids)
Hexane is currently the dominant solvent in the oil extraction industry, valued for its efficiency, low cost, and ability to preserve the quality of oils and proteins. However, this solvent poses health and environmental risks due to its toxicity. Recently, EFSA recommended a reevaluation of hexane as a processing aid due to gaps in toxicity studies and population exposure data. Consequently, a reduction in tolerated residue limits or usage restrictions can be anticipated, potentially leading industrialists to consider alternative solutions. The series of articles introduced here aims to examine the potential consequences of replacing hexane with alternative solvents listed in Directive 2009/32/EC. This comprehensive dossier, comprising eight articles, thoroughly investigates various critical aspects of oilseed extraction. The series explores physicochemical properties (Part 1), safety considerations (Part 2), processing impacts (Part 3), energy consumption (Part 4), oil quality (Part 5), protein meal quality (Part 6), technological comparisons (Part 7), and alternative extraction technologies (Part 8). This in-depth exploration provides a holistic analysis of the challenges and opportunities associated with transitioning from hexane to alternative solvents in the oilseed extraction industry.